Analisis Good Governace Pada Pelayanan E-Pasport - Munigar, Widiya; Karniawati, Nia (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
The porpuse of the research is to determine the quality of servicein the government apparatus based electronic passport, in this study using 5 indicators that tangible, Responsiviness, Realibility, Assurance, and Empathy. And alsosee at the factors that influence the quality of service indicators Organizations, Human Resource, and Service System. The methoduse disdescriptive quantitative method using frequency distribution, and the data collection were interviews, observation, documentation andquestionnaires. With research sites at the Immigration Office Class 1 Bandung. Results ofthe research is that thequality of service in thegovernment apparatus based electronic passport given tothe publicis Very Good”as indicated by the scale 4.21cumulative indexofthe highest value 5.The variables that have the highest value is in the variable Assurance (Warranty) with a score value of 4.60 with the category of “Very Good” and the variable that gets the lowest score by the public is the variable empathy with a score value of 3.97although the category of “Good”. As for the factor of influence in the organization’s services are among the factors, for cesor human resources and service system. Then there commendations givent o the immigration office in Bandung is in grade 1 to further enhancethe quality of His ministry, especially in the Empathy dimension of hospitality, courtesy and discriminatory actions in serving.